Kepemimpinan Kepala Madrasah dalam Meningkatkan Kualitas Pendidikan - M Hadi Purnomo (FALASIFA : Jurnal Studi Keislaman, 2017)
ABSTRACT In the context of leaders of educational institutions, should be distinguished from the leader in a company, given, the product and the appointment are different. Educational leaders have a focus on making people educated while corporate leaders have a focus on creating excellent products. Object is human versus goods. That is why the leader of the educational institution is not only related to can or not, competent or not, qualified or not, but there must be commitment that comes from the heart. Because that would be designed is his heart and then his mind. This paradigm is not much understood by some principals of Madrasahs in educational institutions. Keyword: Leadership of Madrasah Principals, Leadership Effectiveness